Cardiac manifestations of tuberculosis in a tertiary care center of Nepal - Shakya, Smriti; Jha, Sunil Chandra (Nepalese Heart Journal, 2018)
Background and Aims: Tuberculosis remains an important etiological cause of pericarditis and pericardial effusion in developing countries like Nepal. The objective of this study is to identify the various presentations of tuberculous pericarditis along with the demographic profile in our context and their short term outcome. Methods: We studied 53 patients from September 2015 to August 2017 regardless of age and gender who presented to Manmohan Cardiothoracic Vascular and Transplant Center with pericarditis of tubercular origin. The various manifestations of the disease were categorized with 2D echocardiography. Pericardiocentesis was done in patients with large pericardial effusion especially in cardiac tamponade and pericardiectomy done in chronic constrictive pericarditis(CCP). Antitubercular therapy with steroids was instituted. Results: Out of 53 patients, 62% were male and 38% were female. The ages ranged from 6-71 years (42±19.5). Twenty three percent of patients were from the age group 61-70yrs, 20% seen in age group 21-30 years, 8% in less than 10 yrs and 2% in above 70yrs old patients. The most common manifestation seen was large pericardial effusion (32%), followed by CCP (22.6%), 19% presented in cardiac tamponade, 2% had pyopericardium, 2% had perimyocarditis and 4% had acute pericarditis. Adenosine deaminase (ADA) was positive in 75% of the cases when pericardial fluid was tapped. Two patients developed CCP during follow up. Two patients succumbed to death during hospital stay. Conclusion: A high index of suspicion of tubercular pericarditis is inevitable in our settings where other sophisticated investigations are still lacking. Nepalese Heart Journal 2018; 15(1) 35-38